Acute heart failure: a mechanism underscoring sex differences in outcomes following acute coronary syndromes. (14th October 2021) - Cenko, E; Yoon, J; Van Der Schaar, M; Bergami, M; Manfrini, O; Vasiljevic, Z; Zdravkovic, M; Stankovic, G; Vavlukis, M; Kedev, S; Milicic, D; Badimon, L; et al.
Abstract: Background: It remains uncertain whether female sex is itself a strong risk factor for worse outcomes in acute coronary syndromes (ACS). Purpose: We hypothesized that sex differences in vulnerability to heart failure after ACS may modify the association between sex and outcomes. Methods: Data were drawn from the ISACS-Archives network of registries. The study population consisted of 87, 812 patients with known time from symptom onset to hospital presentation. Participants were stratified by ACS subtypes: STEMI and NSTE-ACS Data on presenting heart failure symptoms were collected from medical record abstraction. Heart failure was categorized as Killip class >2. Time from symptom onset to hospital presentation was categorized as early (≤120 minutes) or late (>120 minutes). Primary outcome measure was 30-day mortality. Estimates were performed using a parametric balancing strategy by weighting and compared by test of interaction on the log scale. Results: Among the study sample, 30922 (35.2%) patients were women. Patient outcomes varied according to subtype of ACS. The mortality rates at 30-days were significantly higher among women vs men in STEMI (RR:1.65; 95% CI: 1.56–1.73) compared with NSTE-ACS (RR:1.18; 95% CI: 1.09–1.28; P interaction <0.0001). Similarly, the women vs men RR of heart failure was higher in STEMI (RR: 1.24; 95% CI: 1.20–1.29) compared with NSTE-ACS (RR:1.02; 95% CI: 0.97–1.08; P interaction <0.0001). Sex difference in heart failure rates with STEMI presentation were independent (P<0.0001) of early (34.3% in women vs 24.2% in men) or late (35.5% in women vs 30.7% in men) hospital presentation. The same finding was not seen in NSTE-ACS patients. Overall, women presenting with heart failure was had higher 30-day mortality than did their male counterparts with heart failure (29.8% vs 25.5%; RR: 1.24; 95% CI: 1.17–1.31). Conclusions: Women exhibit substantially more vulnerability to heart failure in STEMI than men: a greater percentage of women have heart failure, and women with heart failure have higher 30-day mortality than men with heart failure. This finding was not seen in NSTE-ACS. heart failure on initial assessment is a key feature to explain the sex gap in mortality after ACS. Funding Acknowledgement: Type of funding sources: None.